LEADER’S REPUTATION AND BUDGETARY SLACK: THE ROLE OF TRUTHFULNESS OF SUBORDINATE - Febriati, Febriati; Yunita, Dhea Rizki (Jurnal Riset Akuntansi dan Keuangan, 2021)
Prior research focusing on informal budget control systems is still limited, so this research is important to be conducted by researchers. In addition, there was a deficit problem that occurred in the West Bandung Regency government budget in 2019 showing an inaccurate budget estimate, so it was issued to discuss the budgetary slack. This study aims the effect of subordinates' truthfulness of the relationship between leader’s reputation and budgetary slack. This study uses a laboratory experiment method with participants being Accounting Students at Panca Bhakti University. A data analysis technique used two-way ANOVA with 2x2 factorial experimental design. The results showed that (1) the influence of leader’s reputation affected on the budgetary slack, (2) subordinates’ truthfulness affected on the budgetary slack, (3) subordinates’ truthfulness affected on the relationship between leader’s reputation and budgetary slack, (4) in favourable leader’s reputation condition, high subordinates’ truthfulness would reduce budgetary slack compare to low subordinates’ truthfulness, and (5) in conditions of high subordinates’ truthfulness, the favourable leader’s reputation would reduce budgetary slack compared to the unfavourable leader’s reputation